The Influence of Social Media Content on Gender Stereotypes Among University Students: A Case Study of Uganda Christian University Students - Gift Nangonde Kalikulali (Uganda Christian University, 2026)
This study explored the influence of social media content on gender stereotypes among university students, focusing on first-year students in the School of Journalism, Media and Communication at Uganda Christian University (UCU). The research aimed to examine how social media shapes students’ perceptions of gender roles, identify challenges that hinder the reduction of gender stereotypes, and propose recommendations for using social media to promote gender equality. The study employed a qualitative research approach, using structured and unstructured questionnaires and interviews. From a class of 27 students, a purposive sample of six participants was selected to provide in‑depth insights relevant to the study objectives. Findings revealed that social media has a notable impact on students’ understanding of gender roles. While certain content reinforces traditional stereotypes, other content challenges these norms and promotes equality. Students also expressed that different forms of social media content influence individuals in varied ways depending on personal exposure and interpretation. Challenges identified included persistent gender stereotypes in online spaces, cultural expectations, and the lack of diverse representation. The study concludes that although social media possesses strong potential to support positive change, its full influence in challenging gender stereotypes requires deliberate effort. It recommends the creation and promotion of content that highlights diverse gender roles, strengthens awareness, and encourages balanced narratives to support an inclusive and stereotype‑free media environment for students.
Undergraduate